Pemekaran Kecamatan Sebagai Jalan Pengakuan Masyarakat Adat di Kabupaten Tana Toraja - Mundi, Moris; Tamma, Sukri; Yunus, Ariana (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This study examines the dynamics of transformation within the Gandangbatu Sillanan community in Tana Toraja Regency, tracing their shift from an administrative entity toward recognition as an indigenous territory. The main issue focuses on how colonial structures of power that placed Gandangbatu Sillanan under the Mengkendek District shaped the state’s way of seeing and governing indigenous domains, as well as how local communities responded through strategies of resistance and negotiation. This research employs a qualitative method, using data collection techniques through interviews and document studies, analyzed within the theoretical framework of political anthropology as proposed by James C. Scott. The findings reveal that the establishment of the Gandangbatu Sillanan District in 2007 represents a form of resistance successfully institutionalized through the bureaucratic channels of the state. This action reflects the indigenous community’s effort to rearticulate local identity and sovereignty within the framework of modern state law. In conclusion, the struggle of the Gandangbatu Sillanan community exemplifies the practice of everyday resistance within the context of Seeing Like a State, where local actors employ state instruments to reaffirm their existence and indigenous autonomy.